Fratture periprotesiche di spalla: trattamento conservativo - Leo, R.; Fogliata, V.; Marelli, N.; Marelli, B.M. (Lo Scalpello - Journal, 2018)
PERIPROSTHETIC SHOULDER FRACTURES: CONSERVATIVE TREATMENT The incidence of periprosthetic shoulder fractures varies from 1 to 3%. The following criteria must be considered for a conservative treatment: (1) stability of the prosthesis; (2) scrambling; and (3) localisation. Conservative treatment plays a marginal role, but knowledge of these criteria will help the surgeon choose the correct treatment, in order to avoid surgery that, sometimes, may be useless and potentially dangerous.